2007
DOI: 10.2136/sssaj2006.0028
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Sorption and Release in a Sandy‐Loam Soil as Influenced by Fertilizer Sources

Abstract: Soil phosphate (PO4–P) sorption and release is affected by reactions at the solution–soil surface interface. The objective of this study was to determine how the net negative surface charge and phosphate adsorption/desorption processes in a sandy‐loam soil were affected by cattle manure and inorganic fertilizer applications. The soil came from a field experiment where manure and triple superphosphate (TSP) were applied annually on an equivalent plant‐available P basis. After 4 yr, manured soils had 37% more ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 28 publications
1
42
3
Order By: Relevance
“…In the case of the ORG farms surveyed in this study, it was considered that a certain amount of organic fertilizer was added to make up the scrimpy fertility effect compared with chemical fertilizer. Furthermore, several studies also reported an increase in available phosphorus upon ORG amendment 16,20,22) . Jiao et al described that organic acids derived from manure, chelate Fe and Al oxides, result in leaching thereby reducing the number of binding sites for phosphate on the surface of soils 16) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the ORG farms surveyed in this study, it was considered that a certain amount of organic fertilizer was added to make up the scrimpy fertility effect compared with chemical fertilizer. Furthermore, several studies also reported an increase in available phosphorus upon ORG amendment 16,20,22) . Jiao et al described that organic acids derived from manure, chelate Fe and Al oxides, result in leaching thereby reducing the number of binding sites for phosphate on the surface of soils 16) .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies also reported an increase in available phosphorus upon ORG amendment 16,20,22) . Jiao et al described that organic acids derived from manure, chelate Fe and Al oxides, result in leaching thereby reducing the number of binding sites for phosphate on the surface of soils 16) . Therefore, the available phosphorus released from soil particles accumulates in the soil, thus resulting in higher concentrations of available phosphorus in ORG soils.…”
Section: Discussionmentioning
confidence: 99%
“…Each factorial plot was split into four strips (20 m by 6 m) and four fertilizer treatments [0,5,10 and 15 Mg ha (1 (dry weight basis) of composted cattle manure] were applied randomly to the split plots. As described by Jiao et al (2007), the 15 Mg ha (1 compost application provided 45 kg plant-available P ha (1 , equivalent to silage corn P requirements. Plots received supplemental inorganic fertilizers, and the target nutrient inputs were 200 kg N ha .…”
Section: Methodsmentioning
confidence: 99%
“…Compost containing treatments reduced PSI and increased MBC and DOC. A combination of anion sorption site saturation with added phosphate, competitive inhibition of anion sorption sites by organic acid anions, reduction of Al 3+ activity through chelation, and reductions in exchangeable acidity via exchange of surface hydrogen by Ca 2+ likely contributed to reduce sorption in soils receiving compost (Iyamuremye et al, 1996a;Nziguheba et al, 1998;Hunt et al, 2007;Jiao et al, 2007). Labile Pi showed a strong correlation with PSI, as anion sorption sites occupied with labile Pi inhibited additional sorption.…”
Section: Phosphorus Source Effects On Biogeochemical Factorsmentioning
confidence: 98%